Sexual and physical intimate partner violence among women using antenatal care in Nampula, Mozambique - Eusébio Chaquisse; Sílvia Fraga; Paula Meireles; Glória Macassa; Joaquim Soares; Francisco Mbofana; Henrique Barros (AOSIS, 2018)
The aim was to estimate the prevalence of sexual and physical intimate partner violence (IPV) and its associated factors, in a sample of pregnant women using antenatal care (ANC) in Nampula province - Mozambique. This cross-sectional study was carried out in six health units in Nampula, from February 2013 to January 2014. Overall, 869 participants answered the Conflict Tactics Scale 2. The lifetime and past year prevalence of sexual abuse was 49% and 46%, and of physical abuse was 46% and 44%, respectively. Lifetime and past year sexual abuse was significantly associated with living as a couple, alcohol drinking and having a past diagnosis of gonorrhea. Lifetime and past year physical abuse increased significantly with age and was associated with living as a couple, alcohol drinking and history with syphilis. The prevalence of lifetime and previous year violence among women using ANC was high and similar showing that most women were constantly exposed to IPV. ANC provides a window of opportunity for identifying and acting on violence against women.